2021
DOI: 10.3390/healthcare9081068
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucosa Could Be an Infectious Target of SARS-CoV-2

Abstract: The World Health Organization reported that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is caused by respiratory droplets and aerosols from the oral cavity of infected patients. The angiotensin-converting enzyme 2 (ACE2) is considered the host functional protein for SARS-CoV-2 infection. In this article, we first revealed that the positive proportion of ACE2 expression in gingival cells collected from the gingival sulcus was increased to the same level as the tongue. Our data demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
4
20
0
2
Order By: Relevance
“…This would lead to subsequent cytokine response of cells of oral cavity of individuals with hyperglycemia. This observation is in agreement with the fact that hyperglycemia is a co-morbidity in SARS-CoV2 viral infection [41][42][43] and the virus gains entry into the host cells through cells of the nose and oral cavity [44] which express ACE2 and TMPRSS2.…”
Section: Mhct08-e Grown In High Glucose Medium Showed Increased Ace2 ...supporting
confidence: 88%
“…This would lead to subsequent cytokine response of cells of oral cavity of individuals with hyperglycemia. This observation is in agreement with the fact that hyperglycemia is a co-morbidity in SARS-CoV2 viral infection [41][42][43] and the virus gains entry into the host cells through cells of the nose and oral cavity [44] which express ACE2 and TMPRSS2.…”
Section: Mhct08-e Grown In High Glucose Medium Showed Increased Ace2 ...supporting
confidence: 88%
“…Since the blockage of SARSā€CoVā€2 cell entry in HEK293Tā€ACE2 and virusā€cell fusion assay in CHOā€K1 cells could also be due to the potential toxicity associated with the ORs, we next evaluated the potential side effect of the ORs by measuring the release of LDHā€”an enzyme, which is an indicator of cellular toxicity (Okui et al, 2021 ). In this experiment, we tested the impact of both the ORs separately on CHOā€K1 and HEK293Tā€ACE2 cells using multiple dosages and the two critical time points (15 min and 48 h).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to ACEā€2, multiple other cell surface receptors and coā€receptors have also been proposed to support SARSā€CoVā€2 entry (Gadanec et al, 2021 ; Sigrist et al, 2020 ; Tiwari, Beer, et al, 2020 ; Tiwari, Tandon, et al, 2020 ). The ACE2 receptors are highly expressed in nasopharyngeal tissues and the oral cavity (Okui et al, 2021 ; Sawa et al, 2021 ; Xu et al, 2020 ; Zhong et al, 2020 ). Interestingly, the expression levels of ACE2 receptors vary depending on age, gender, and certain predispositions (Drozdzik & Drozdzik, 2022 ; Okui et al, 2021 ; Peng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okui et al confirmed ACE2 immunolocalization in gingival cells collected from the gingival sulcus (and quantified to the same level as the tongue, which was formerly considered as one on the main SARS-CoV-2 entry routes, along with the salivary glands). The expression level of ACE2 in the keratinized mucosa of the palate was documented to be very mild [9].…”
Section: Oral Cavity As the Sars-cov-2 Entry Gateway 21 Oral Mucosamentioning
confidence: 99%